Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Given
[tex]25x^{-4} - 99x^{-2} - 4 = 0[/tex]
consider substituting [tex]y=x^{-2}[/tex] to get a proper quadratic equation,
[tex]25y^2 - 99y - 4 = 0[/tex]
Solve for [tex]y[/tex] ; we can factorize to get
[tex](25y + 1) (y - 4) = 0[/tex]
[tex]25y+1 = 0 \text{ or } y - 4 = 0[/tex]
[tex]y = -\dfrac1{25} \text{ or }y = 4[/tex]
Solve for [tex]x[/tex] :
[tex]x^{-2} = -\dfrac1{25} \text{ or }x^{-2} = 4[/tex]
The first equation has no real solution, since [tex]x^{-2} = \frac1{x^2} > 0[/tex] for all non-zero [tex]x[/tex]. Proceeding with the second equation, we get
[tex]x^{-2} = 4 \implies x^2 = \dfrac14 \implies x = \pm\sqrt{\dfrac14} = \boxed{\pm \dfrac12}[/tex]
If we want to find all complex solutions, we take [tex]i=\sqrt{-1}[/tex] so that the first equation above would have led us to
[tex]x^{-2} = -\dfrac1{25} \implies x^2 = -25 \implies x = \pm\sqrt{-25} = \pm5i[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.